Noise-like pulse generation in erbium-doped fiber laser by hybrid mode-locking of graded index multimode fiber and nonlinear optical loop mirror - Maad, Hikmat; Mohd Yusoff, Norita; Ahmad Anas, Siti Barirah; Mokhtar, Makhfudzah; Mahdi, Mohd Adzir; Zan, Zuraidah (Academic Press, 2025)
The practical implementation of graded-index multimode fiber (GIMF) as a saturable absorber (SA) in mode-locked fiber lasers is limited by the requirement for extremely short fiber lengths, making its reproducibility and investigation difficult. In this work, we demonstrate stable noise-like pulse (NLP) generation using a hybrid mode-locked fiber laser that integrates a nonlinear optical loop mirror (NOLM) with a 32 m GIMF segment. Nonlinear multimode interference (NL-MMI) and nonlinear phase accumulation within the NOLM bidirectional-loop (bi-loop) were leveraged to enhance the saturable absorption characteristics. Comprehensive measurements comparing the nonlinear transmission behavior of GIMF alone and NOLM-GIMF structures confirmed a substantial improvement in modulation depth. NLP generation was systematically investigated across GIMF lengths from 30 m to 62.5 m, with optimal performance observed at 32 m, yielding a 3-dB bandwidth of 22.38 nm, spike width of 153.9 fs, and pedestal width of 61.73 ps. The obtained pulse is significantly shorter than previously reported NLP, which is typically reported in the nanosecond range for the 1.5 µm regime. Long-term stability testing over 300 min showed minimal spectral and temporal fluctuations, confirming robust operation. The proposed NOLM-GIMF design successfully overcomes the short-length constraint of GIMF-based SAs, offering a scalable and reliable solution for high-energy, broadband NLP fiber lasers in the 1.5 µm regime. This work advances mode-locked fiber laser technology by improving stability and scalability for ultrafast photonics applications.